NOMINA KOSMIS DALAM BAHASA JAWA - Ashari Hidayat (Sunan Kalijaga State Islamic University Yogyakarta, 2010)
Cosmic nouns in Javanese language are a group of nouns, which refers to astronomic and geographic notion. This research aims at describing its morphologic and syntactic characteristics. This research uses distributional and equivalent method. The data is collected from everyday use of language as well as its variety of the language, literature, and dictionary. The astronomic nouns refer to